ANALYSIS OF INTERCULTURAL COMMUNICATION IN A MULTICULTURAL ENVIRONMENT: A CASE STUDY OF MUSLIM AND NON-MUSLIM STUDENT INTERACTION IN ACADEMIC AND SOCIAL ACTIVITIES AT MUHAMMADIYAH UNIVERSITY OF NORTH SUMATRA - Mardiana Siagian; Muhammad Husni Ritonga (Program Pascasarjana UIN Sumatera Utara, 2025)
This study aims to analyze intercultural communication between Muslim and non-Muslim students within the multicultural environment of Universitas Muhammadiyah Sumatera Utara (UMSU). In both academic and social interactions, cultural and religious diversity can be both a potential and a challenge in establishing effective communication. This research employs a qualitative approach using a case study method, with data collected through in-depth interviews, participant observation, and documentation. The findings reveal that the effectiveness of intercultural communication is influenced by several factors, including individual cultural competence, empathy and openness, stereotypes and prejudices, religious symbols, and the campus social environment. The forms of communication observed include formal and informal verbal communication, non-verbal communication, and symbolic cultural and religious expressions. The study concludes that successful intercultural communication requires institutional support, inclusive interaction spaces, and mutual respect among students. These findings are expected to serve as input for higher education institutions in strengthening multicultural and tolerant practices on campus.